2015
DOI: 10.1007/s11739-015-1370-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between left ventricular mechanics and low free triiodothyronine levels after myocardial infarction: a prospective study

Abstract: Low free triiodothyronine (fT3) levels following acute myocardial infarction (AMI) are associated with greater impairment in cardiac mechanics compared with patients with AMI who have normal values of thyroid hormones. The objectives are to investigate left ventricular (LV) function and mechanics during a 6-month follow-up after myocardial infarction and to evaluate their prognostic implication using two-dimensional (2D) echocardiography and 2D speckle-tracking echocardiography in patients with low fT3 levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…The underlying mechanism has not yet been fully elucidated, several plausible explanations are stated as follows. First, as stated above, low FT3 may be an marker reflecting severe cardiac damage, in which extensive cardiac damage had greater impairment of cardiac function, further declining cardiac output and reducing renal blood flow, and deteriorated renal function [32]. Second, low FT3 level was also considered to be a maladaptive neurohumoral alteration during acute ill condition, for that lower FT3 level contributed to the preservation of energy yet in turn weakened the regeneration and self-repair capability of tubular epithelium [29,33].…”
Section: Discussionmentioning
confidence: 97%
“…The underlying mechanism has not yet been fully elucidated, several plausible explanations are stated as follows. First, as stated above, low FT3 may be an marker reflecting severe cardiac damage, in which extensive cardiac damage had greater impairment of cardiac function, further declining cardiac output and reducing renal blood flow, and deteriorated renal function [32]. Second, low FT3 level was also considered to be a maladaptive neurohumoral alteration during acute ill condition, for that lower FT3 level contributed to the preservation of energy yet in turn weakened the regeneration and self-repair capability of tubular epithelium [29,33].…”
Section: Discussionmentioning
confidence: 97%
“…Wang et al (25) showed that fT 3 was significantly and negatively correlated with lg-CKMB and lg-TnI, indicating that a lower fT 3 level is correlated with a more severe cardiac injury in the ST segment elevation MI (STEMI) patients. In another study, Jankauskienė et al (26) demonstrated that low fT 3 levels were significantly associated with worse left ventricular (LV) mechanics and important for the prediction of the LV structure and function after MI. Furthermore, low T 3 is known to affect the short-term and long-term prognosis of patients with cardiovascular disease, including STEMI (27), heart failure (28), and coronary artery bypass grafting (29).…”
Section: Discussionmentioning
confidence: 99%
“…Following administration of THs in these acute conditions, myocardial dysfunction associated with loss of high-energy phosphates and accumulation of tissue lactate was reversed. Although total T3 is frequently used, free T3, is now understood to be a clinically important biomarker in cardiovascular disorders and is the active form of the hormone (Iervasi et al, 2003; Fontana et al, 2012; Cerillo et al, 2014; Kishi, 2015; Jankauskiene et al, 2016; Wang et al, 2016). While 8 μg/kg/day showed increased serum free T3 levels, 4.5 μg/kg/day did not, indicating that the lower dose is both a safer cardiac dose and free T3 may be a clinically relevant biomarker for monitoring during T3 therapy.…”
Section: Discussionmentioning
confidence: 99%